Potensi Ekstrak Lengkuas (Alpinia Purpurata K. Schum) Sebagai Fungisida Terhadap Jamur Alternaria Sp. Pada Tanaman Jeruk - Mia Nurkanti; Mimi Halimah; Yosi Silfister; Handi Suganda (Biotropic : The Journal of Tropical Biology, 2020)
Alternaria sp. is one the causess of diseases that attack citrus crops. Pest and diseases control efforts by farmers more often use pesticide synthesis. This study aims to determine the inhibition of mushroom growth and other benefits of galangal extract as a natural fungicide and determine the optimum concentration of galangan extract inhibiting the growth mushroom of Alternaria sp.. The method used was experimental, testing conducted by growing mycelium mushroom Alternaria sp. on a PDA that has been mixed with extract of galangal in according to the respective concentrations and analyze growth response by measuring the diameter. The best results indicated by the treatments 60% that control the growth of mushrooms with deaths amounted to 79%. This shown that galangal extract is able to control the growth of Alternaria sp. at concentrations 60% compared to a concentration of 20%, 30%, 40% and 50% because the active compounds at concentrations that are 60% higher, so galangal extract diffuse into the cell the growing of mushrooms and may cause disruption the growth mushrooms Alternaria sp.. The higher concentration of extract given, the ability to controlling the growth mushroom of Alternaria sp. the better. The utilization of galangal material is done as an alternative fungicide in the control of plant diseases that are eco friendly.